Four-corner outcomes in strategic management: Successful and unsuccessful paddling down versus upstream - Woodside, Arch; Nagy, G.; Megehee, C. (2018)
Copyright © 2018 by Emerald Publishing Limited. This chapter elaborates on the usefulness of embracing complexity theory modeling outcomes rather than directionality, and modeling complex rather than simple outcomes in strategic management. Complexity theory includes the tenet that most antecedent conditions are neither sufficient nor necessary for the occurrence of a specific outcome. Identifying a firm by individual antecedents (i.e., noninnovative vs. highly innovative, small vs. large size in sales or number of employees, or serving local vs. international markets) provides shallow information in modeling specific outcomes (e.g., high sales growth or high profitability)-even if directional analyses (e.g., regression analysis, including structural equation modeling) indicate that the independent (main) effects of the individual antecedents relate to outcomes directionally-because firm (case) anomalies almost always occur to main effects. Examples: A number of highly innovative firms have low sales while others have high sales and a number of noninnovative firms have low sales while others have high sales. Breaking-away from the current dominant logic of directionality testing-null hypothesis significance testing (NHST)-to embrace somewhat precise outcome testing (SPOT) is necessary for extracting highly useful information about the causes of anomalies-associations opposite to expected and "statistically significant"main effects. The study of anomalies extends to identifying the occurrences of four-corner strategy outcomes: Firms doing well in favorable circumstances, firms doing badly in favorable circumstances, firms doing well in unfavorable circumstances, and firms doing badly in unfavorable circumstances. Models of four-corner strategy outcomes advance strategic management beyond the current dominant logic of directional modeling of single outcomes.